XPS-Surface Analysis of SEI Layers on Li-Ion Cathodes: Part II. SEI-Composition and Formation inside Composite Electrodes. Issue 5 (1st January 2018) - Schulz, Natalia; Hausbrand, René; Wittich, Carolin; Dimesso, Lucangelo; Jaegermann, Wolfram
Abstract : In this contribution, we investigate the solid electrolyte interface (SEI) layers' composition depending on the spatial location within LiCoO2 composite cathode of a commercial Li-Ion battery. The surface chemistry is analyzed by X-ray photoelectron spectroscopy (XPS), and possible SEI morphology and the differences in the SEI composition are discussed in detail. Finally, related SEI formation reactions and the controlling processes are characterized as a function of the depth in the composite cathode. The SEI is assumed to be a multi-component, layered system. The inorganic inner SEI layer consists of LiF and degraded LiCoO2, confirmed as Co(II, III)x Oy (OH)z . The much thicker outer SEI layer is mainly composed of a poly-organic network with a significantly smaller portion of, presumably, randomly distributed macroscopic Lix POy Fz /Lix POy-1 Fz+1 and Lix POy domains. A higher content of Co(II, III)x Oy (OH)z, and especially of the poly-organic deposit, was found on the outer cathode surface compared to the analysis position near the current collector, resulting in a 4 nm thicker SEI and indicating a stronger decomposition of LiCoO2 and solvents. These differences in SEI composition and thickness are attributed to a significantly higher cathode polarization at the outer electrode surface during cell operation leading to a higher rate of electrochemically induced decomposition reactions.